Persepsi Wisatawan Terhadap Destinasi Wisata Di Pulau Sara Kabupaten Kepulauan Talaud - Rembaen, Rania Gratia Plena; Kapantow, Gene Henfried Meyer; Talumingan, Celsius (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The aim of this research is to determine tourists’ perceptions of tourist destinations on Sara Island, Talaud Islands Regency. The perception of tourists visiting the Sara Island tourist destination is measured based on five factors that a tourist destination needs to have, namely perception of attractions, perception of facilities, perception of infrastructure, perception of transportation, and perception of hospitality. The sampling method in this research is using the Accidental Sampling method. Data was collected through interviews using a questionnaire, tourists’ perceptions were measured using a Likert scale of 1 to 4. The data was processed descriptively. The results of this research show that tourists’ perceptions of the Sara Island tourist destination are generally at a good and very good level. Except for road and electricity infrastructure which is still not good. Of the good indicators, there are two indicators whose scores are quite low, namely cottage facilities and the availability of clean water. Therefore, in addition to the two indicators that received unfavorable perceptions, these two indicators also needed attention from the management.